PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT - Hexana Lastanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
To be able to achieve good corporate governance, in addition to managerial ownership, institutional ownership and board of directors, the role of the audit committee also needed to further enhance the quality of information contained in the financial statements in accordance with his duties. Good corporate governance is one way to address the practice of earnings management. Study to examine the effect of the mechanisms of good corporate governance on earnings management that uses the data in the Indonesian capital market, still very little is done. Earnings management is a management action in the process of preparing financial statements to influence the level of profit that is displayed. The goal is to improve the welfare of certain parties, which can be identified as an advantage. Earnings management problem is the agency problem that is often triggered by a separation of the role or the difference between the interests of the owners (shareholders) with managing the company's management.